Proteoglycan and Collagen Expression During Human Air Conducting System Development - Pereda-Tapiol, J; Godoy-Guzman, C (Luigi Ponzio e figlio Editori, 2012)
The lung is formed from a bud that grows and divides in a dichotomous way. A bud is a new growth center which is determined by epithelial-mesenchymal interactions where proteins of the extracellular matrix (ECM) might be involved. To understand this protein participation during human lung development, we examined the expression and distribution of proteoglycans in relation to the different types of collagens during the period in which the air conducting system is installed. Using light microscopy and immunohistochemistry we evaluate the expression of collagens (I, III and VI) and proteoglycans (decorin, biglycan and lumican) between 8 to 10 weeks post fertilization and 11 to 14 weeks of gestational age of human embryo and fetus lungs. We show that decorin, lumican and all the collagen types investigated were expressed at the epitheliummesenchymal interface, forming a sleeve around the bronchiolar ducts. In addition, biglycan was expressed in both the endothelial cells and the smooth muscle of the blood vessels. Thus, the similar distribution pattern of collagen and proteoglycans in the early developmental stages of the human lung may be closely related to the process of dichotomous division of the bronchial tree. This study provides a new insight concerning the participation of collagens and proteoglycans in the epithelial-mesenchymal interface during the period in which the air conducting system is installed in the human fetal lung. © Godoy-Guzmán et al.,2012.